PEGylated DPPC/Anti-SNAP25 Antibody Targeted Liposomes from Langmuir Monolayer Study to Formulations - Gew, Lai T.; Misran, Misni (Current Chemical Biology, 2021)
Background: Molecule compatibility is an important factor to be considered before preparing antibody-targeted liposomes, stealth-liposomes, and stealth antibody-targeted liposomes. Objective: To determine the intermolecular interaction of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamide- N-[methoxy(polyethyleneglycol)-2000] (ammonium salt), DOPE PEG2000 and Anti-SNAP25 (AS25) in 1,2-dipalmitoyl-sn-glycero-3-phosphorylcholine (DPPC) monolayer, and their liposomes. Methods: In this study, DPPC was used to create a monolayer mimicking the half membrane of liposomes to investigate its interactions with a polyclonal antibody, AS25, and DOPE PEG2000, which are based on Langmuir-Blodgett (LB) techniques. The surface morphology of DPPC-AS25 and DPPC-DOPE PEG2000-AS25 bilayers were also imaged and analyzed by using atomic force microscopy (AFM) to support the LB findings. The LB findings were then utilized as a reference to prepare DPPC liposomes in this work. Results: The best mole ratio of DPPC-DOPE PEG2000, determined to be 50 to 1, was used to study the interaction with the polyclonal antibody AS25. The free energy of mixing (ΔGmix) of DPPC- DOPE PEG2000-AS25 was more negative than DPPC-AS25 in the entire investigated ranges, indicating that the ternary mixture of DPPC-DOPE PEG2000-AS25 was more compatible than the binary mixture of DPPC-AS25. The presence of DOPE PEG2000 in DPPC-AS25 increased the fluidity of the membrane, which resulted in a greater interaction of AS25 with DPPC. Conclusion: The constant values of particle size and zeta potential measurements of DPPC-DOPE PEG2000-AS25 liposomes showed agreement with the LB findings, indicating that LB is a good technique to predict precise liposomal formulations.
Keywords: drug delivery